PENGARUH BEBAN PAJAK, UKURAN PERUSAHAAN, DEBT COVENANT DAN EXCHAGE RATE TERHADAP TRANSFER PRICING - Rahutomo, Fajar Singgih; Pratiwi, Adhitya Putri (E-Jurnal Akuntansi TSM, 2025)
This study aims to test and analyze the effect of tax burden, firm size, debt covenant and exchange rate on transfer pricing. This type of research is quantitative using secondary data. The population in this study are consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The research sample focused on multinational companies in the sector. The sample selection technique used was purposive sampling, so that from a total of 130 companies, 18 multinational companies were obtained as samples for 5 years, with a total of 90 observation data. The analysis technique used is logistic regression with the help of EViews 13 software. The results showed that simultaneously tax burden, firm size, debt covenant and exchange rate affect transfer pricing. Partially, tax burden and debt covenant affect transfer pricing, while firm size and exchange rate have no effect on transfer pricing.